(untitled) (Research, Society and Development, 2024)
Neurofibromatosis, a genetic condition characterized by the development of benign tumors in nerves and skin, directly impacts the aesthetics and functionality of the face, affecting the quality of life and emotional well-being of patients. Orofacial harmonization (HOF) in patients with neurofibromatosis (NF) presents unique challenges due to the clinical manifestations of the disease, such as skin nodules and facial deformities. The study aims to provide insight into orofacial harmonization in patients with neurofibromatosis through a narrative literature review study. HOF procedures, such as fillers and biostimulators, can minimize facial asymmetries and improve tissue appearance, providing aesthetic and functional benefits. This treatment application requires specialized knowledge of the complications associated with NF, including fibromas, changes in bone growth, and difficulties in healing. Orofacial harmonization can represent a significant improvement in the quality of life of patients with neurofibromatosis, it requires specific care, technical knowledge, and specialized monitoring, highlighting the importance of personalized and multidisciplinary treatments involving dentistry, dermatology, and plastic surgery professionals.